Sustainable Sourcing of Indigenous West-African Seed-oils for Personal Care Applications A case study on the supply chains of baobab and shea - Jensen, Tove; Ahlborg Delvin, Kristine (My University, 2021)
Many West-African oilseeds are resources with untapped potential that could be attractive for the cosmetic industry, baobab (Adansonia Digitata) being one example.Shea (Vitellaria Paradoxa) is an already commercialised indigenous West-African species that plays an important role for rural livelihoods in the region.Some commonly mentioned sustainability aspects of increased utilisation of indigenous trees are the potential to contribute to the local communities and to the conservation of the species. However, since sustainability is a broad and widely used concept,it is important to define what sustainability really means in a specific context. The beauty industry, a growing multi-billion-dollar industry, is seeing intensified consumer demand for natural, clean, and sustainable products.As a result, cosmetic ingredient producers such as the German specialty chemical company Evonik, are investigating new potential raw materials to step wise transform their product portfolio.The purpose of the study is thereby to investigate how commercial activities can be combined with socio-ecological engagement when sourcing and integrating bio-based feed stock in an industrial supply chain. The aim is to, through a case study on baobab and shea, investigate the feasibility and sustainability of sourcing West-African indigenous seed oils as raw materials for cosmetic oils and fatty acids.The project is conducted as a case study using methods such as the product chain organisation study (PCO) and material flow analysis. The PCO enables identification of technical process steps, actors and their role and scope of action in the product chain. The actors’ perspectives on sustainable and ethical sourcing are collected through semi-structured interviews. These perspectives, together with study areas from conventional feasibility studies,creates the foundation for an assessment framework. The framework consists of a set of study areas, for which critical questions and criteria are formulated. As a result,17 study areas and 38criteriaare identified to guide the initiation of feasible and sustainable sourcing.For sourcing baobab and shea as raw materials for cosmetic ingredients, some criteria are already met while others require further activities to be met. The oil processing of baobab highly depends on the oil yield which in turn impacts its applicability as feed stock for cosmetic ingredient manufacturing.The perspectives on sustainable and ethical sourcing both differ and align among the actors involved. Therefore, there is a need to identify what sustainable and ethical sourcing mean for the actors within the product chain. The criteria identified in this study can be used to define what sustainability really means in the specific area of sustainable sourcing. It is evident that sustainable and ethical sourcing are not just “nice to have”,but fundamental to do business. The sourcing scheme suggested in this study presents an opportunity to engage in an unconventional sourcing scheme with unconventional partnerships around unconventional seed-oils with potential to create a positive impact to both people and planet.
Keywords: Indigenous seed-oil; sustainable sourcing; ethical sourcing; product chain organisation study; PCO